(untitled) (European Journal of Teaching and Education, 2021)
The student success in the first year, is influenced, among the other things, even by academic factors: college readiness, core curriculum in high school, cognitive, etc. The alignment analysis of the some core courses between university and high school, is the main objective of this article. The qualitative method and student questionnaires, are used to carry out this analysis. The results obtained indicate the influence of curriculum alignment on classroom teaching and student success for three core courses: Mathematics, Physics and Chemistry, on the first year. Using the regress analyze, some linear relationships are found, either for two classroom teaching and student success indicators as well. Based on these results, we emphasize the necessity for a greater student support during the transition from high school to university, in order to foster student success. This study was conducted in engineering study field, but it can be used in the other fields as well.